PERKEMBANGAN BAHASA INDONESIA DALAM PEMBENTUKAN IDENTITAS NASIONAL DI ERA DIGITAL SEBAGAI DAMPAK GLOBALISASI - Rosadi, Mimi; -, Sutikno (Universitas Muhammadiyah Tapanuli Selatan, 2024)
This research aims to analyze the development of the Indonesian language in the context of the formation of national identity in the digital era and the influence of globalization on the use of the Indonesian language. The research method used is a qualitative method with a descriptive-analytical approach. Data was collected through literature studies and observations of the use of Indonesian in digital media. The research results show that the Indonesian language is experiencing dynamic development which is influenced by digitalization and globalization, both in terms of vocabulary, structure and use in everyday communication.